Authoritarian dimension of judicial ideology of the Slovenian constitutional court - Letnar Černič, Jernej (Array, 2020)
After the democratization and independence of Slovenia, the Constitutional Court has generated the paradigm reform in the Slovenian constitutional system by protecting individual rights against the heritage of the former system. The constitutional judges are not blank slates, but individuals embedded in their private and professional environments. In the past three decades, the Court has delivered several seminal decisions concerning the protection of the rule of law, human rights, and constitutional democracy. What motivates constitutional judges to protect individual rights in some cases and show preference for the preservation of authority and stability of the existing legal system in others? The article is based on the empirical research measuring the presence of judicial ideology at the Constitutional Court of Slovenia in three mandates (1993–1997, 2002–2006, 2011–2016). The methodological and theoretical model aims to measure economic, social, and authoritarian dimensions of judicial ideology (three-fold judicial ideology model). The research group has analysed the decisions and separate opinions of the Constitutional Court from selected periods based on hypotheses provided by the model. This article intends to present and analyse the research results concerning the authoritarian dimension of judicial ideology. More specifically, it examines the level of authoritarianism of the Slovenian Constitutional Court in its judicial decision-making during the three mentioned mandates. Through the obtained empirical results, the paper seeks to strengthen fair, impartial, and independent functioning of the Slovenian Constitutional Court and its respective judges.